Pengaruh Datuk Raja Ahmad Dalam Penyebaran Ajaran Agama Islam Di Pulau Nias - Waslan Haris Tanjug, Nur Aisah Simamora, Abrar M. Dawud Faza (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2021)
This study will examine the influence of Injik Puncak Alam or better known on Nias Island by the name of Datuk Raja Ahmad in the spread of Islamic teachings on the island of Nias. This research is a qualitative research type of field research using historical methods. The data collection techniques in this study used participatory observation techniques with complete participation, semi-structured interview techniques, and used literature studies in the form of photos, literature studies, journals, and online articles about Datuk Raja Ahmad, Nias culture, and Nias history. The results of this study reveal that through the history of the arrival and life of Datuk Raja Ahmad on the island of Nias, he spent more time protechting the people of the island of Nias, especially the coastal areas from pirates. Datuk Raja Ahmad’s greatest influence in spreading the teachings of Islam on the Island of Nias was when he built Kampung Dalam Gunungsitoli and implemented the culture or customs resulting from the assimilation of three cultures, namely: Nias, Aceh, and Minang, which later became known as the Nias Coastal Culture. So according to the author, the influence of Datuk Raja Ahmad in spreading the teachings of Islam on the island of Nias, has simillarities with the influence of the Waliyullah when carrying out Islamic dakwah (spreading/introducing Islam) to the community.